Study of the temperature induced polytype conversion in cubic SiC by Raman spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2004)
Using 3C-SiC crystals grown on undulant Si(100) substrates as seed crystals, bulk growth of 3C-SiC by the modified Lely method has been demonstrated. However, particularly at elevated growth temperatures, macroscopic 6H-SiC inclusions can be observed in the grown crystals. Here we investigate the temperature dependence of the 3C- to 6H-SiC transformation of the CVD substrate by Micro Raman Spectroscopy after annealing at temperatures between 1700°C and 2100°C. At temperatures above 1800°C 3C- to 6H-SiC polytype transformation is observed that proceeds from the top side of the crystals. However, the conversion appears to be stopped at domain boundaries that are oriented along 111 planes.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.IAP.LAP.studyo
Keywords: Annealing CVD; Cubic SiC; Raman spectroscopy